Selenium supplementation on reproductive and productive performance, tissue concentration and glutathione peroxidase activity in sows and piglets : A meta-analysis - Quisirumbay-Gaibor, Jimmy (2021)
The effect of selenium supplementation on reproductive and productive performance, tissue concentration and GSH-Px activity in sows and their progeny was evaluated in a meta-analysis study. Twelve articles were used that included 4698 animals. Under the random effects model, effect size, heterogeneity, meta-regressions and publication bias were determined. Reproductive variables were not affected by the source of selenium. Piglet birth weight was higher (p=0.031) in sows that received inorganic selenium (SeI) 1.47 vs. 1.46 kg from the organic source (SeO). Piglet weaning weight was 135 g greater (p=0.105) in sows from the SeO group. Tissue concentration showed that SeO increases Se to a greater extent in sow blood (0.209 ppm; p<0.00001), colostrum (0.324 ppm; p=0.002), milk (0.145 ppm; p<0.00001) and in tissues of progeny as liver (1.462 ppm; p=0.048) muscle (0.319 ppm; p<0.00001), kidney (1.275 ppm; p=0.004) and blood (0.18 ppm; p=0.005). However, the higher tissue concentration of Se reached by SeO was not sufficient to increase the activity of the enzyme glutathione peroxidase (GSH-Px) in serum in sows (0.912 U / ml; p=0.119) or in piglets (0.286 U/ml; p=0.446). Colostrum (408.78 U/ml; p=0.048) and milk (239.43 U/ml; p<0.00001) presented higher enzymatic activity with SeO. The source of Se supplemented in the diet does not make a difference in reproductive performance in sows. SeO generates a higher tissue concentration in sows and their progeny. GSH-Px activity does not show differences in sows or piglets, but not in colostrum and milk.